Conventional amphotericin B elicits markers of immunogenic cell death on leukemic blasts, mediates immunostimulatory effects on phagocytic cells, and synergizes with PD-L1 blockade. (31st December 2022) - Kofla, G.; Radecke, C.; Frentsch, M.; Walther, W.; Stintzing, S.; Riess, H.; Bullinger, L.; Na, I-K.
ABSTRACT: Immunostimulatory regimens are a game changer in the fight against cancer, but still only a minority of patients achieve clinical benefit. Combination with immunomodulatory drugs and agents converting otherwise non-immunogenic forms of cell death into bona fide "immunogenic cell death" (ICD) could improve the efficacy of these novel therapies. The aim of our study was to investigate conventional Amphotericin B (AmB) as an enhancer of antitumor immune responses. In tumor cell line models, AmB induced ICD with its typical hallmarks of calreticulin (CALR) expression and release of high mobility group box 1 (HMGB1) as well as Adenosine 5'-triphosphate (ATP). Interestingly, in contrast to non-ICD inducing treatments, ICD induction led to up-regulation of PD-L1-expression by ICD experiencing cells, resulting in decreased maturation of dendritic cells (DCs). Blocking this PD-L1 expression on tumor cells could unleash full ICD effects on antigen presenting cells. Even at sub-toxic concentrations, AmB was able to enhance CALR on leukemic blasts, particularly on phagocytic monoblastic THP-1 cells, which also showed features of "M1-like" differentiation after AmB exposure. The ability of AmB to increase the immunogenicity of tumor cells was confirmed in vivo in a mouse vaccination experiment. In conclusion, we demonstrate that AmB can promote antitumor immune responses in a dose-dependent manner by ICD induction, surface translocation of CALR on leukemic blasts even at sub-toxic concentrations, and "M1-like" polarization of phagocytic cells, making it noteworthy as potential booster for cancer immunotherapy. We additionally report for the first time that PD-L1 expression may be a feature of ICD, possibly as a negative feedback mechanism regulating the maturation status of DCs and thus indirectly affecting T-cell priming.